UTILIZATION OF VARIOUS MICROORGANISMS IN CHEESE MAKING AS AN APPLICATION OF INDUSTRIAL BIOTECHNOLOGY - Ifa Ana Meilani; Ainun Nafiatus Ulfah, Alifia Hasna Azzah Fillah, Evria Asih, Hanasari Faida Pranama, Atip Nurwahyuna (Adisam Publisher, 2024)
Cheese is a type of food produced by separating solid substances in milk through a process of thickening or coagulation. The cheese-making process generally involves the use of bacteria from the Actinobacteriaceae group. This study utilizes a literature review method, including the analysis of several relevant articles, and is further analyzed using a descriptive-analytical approach. The methodological steps involved searching Google with the keywords